FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI DALAM BERUSAHATANI PADI DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Ardiyono Muhammad; Agustono Agustono; Arip Wijianto (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The research aims are (1) Analyse cost, revenue and income (2) Efficiency farming (3) Analyse the factors influencing interest farmers in the cultivation of rice in Kebakkramat  district  Karanganyar.  The  basic  method  of  this  research  used  the explanatory  method.  Research  locations  are  Kebakkramat  district  Karanganyar. Method of the sample collection that is purposive sampling with the sample of the 60 farmers. The data used in this research are primary and secondary data. Methods of data analysis used in this research are (1) Analysis of cost, Revenue and Income (2) Efficiency  Analysis  (3)  Binary  Logistic  Regression.  The  results  showed  that  (1) Average cost of seeking Rp 4.457.348 per UT or Rp  9.682.870 per Ha, revenue of Rp 12.749.167 per UT or Rp 27.695.510 per Ha, earn an income of Rp 8.291.819 per UT or  Rp  18.012.641  per  Ha  (2)  Farm  efficiency  of  2.89  (3)  Variables  influential  real with an odd ratio: Variable commodity prices , variable price seed , variable the price of  fertilizer  and  variable  the  availability  of  water.  While  variables  which  not influential  real:  Variable  area  of  land,  variable  experience,  variable  age,  variable education, variable government assistance, and variable alternation planting.